PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PROSES PERADILAN PIDANA DI WILAYAH HUKUM POLDA METRO JAYA - Yenny Silvia Sari Sirait (Jurnal Idea Hukum, 2017)
Human Traficking is the worst violation of human rights. This study aims to analyze the loss and/or the suffering of victims of human trafficking, criminal law policy governing the legal protection of victims of human trafficking and its implementation in the process of criminal justice at the Polda Metro Jaya’s jurisdiction. The method used in thi research is the juridical sociological conducted by interviewing respondents, an inventory and study the legislation, as well as literature study. Losses and/or the suffering experienced by the victims of human traficking include loss of material, psychological, physical and social. The legal protection given to victims of human trafficking in the criminal justice process based regulated in various legislations. Implementation of legal protection for victims of human trafficking in the criminal justice process at Polda Metro Jaya’s jurisdiction during the criminal justice process is always given and is not always given.